PENGARUH BRAND CREDIBILITY DAN BRAND EXPERIENCE TERHADAP BRAND LOYALTY YANG DIMEDIASI OLEH ATTITUDE TOWARDS BRAND - Monika Monika; Kurniawati Kurniawati (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to analyze how the influence of Brand Credibility and Brand Experience on Brand Loyalty, either directly or through mediation through Attitude Towards Brand. Methodology: Design of this research is cross sectional where data is collected from respondents at a certain time, data collection uses side simple random to 232 respondents randomly in Indonesia, data analysis method uses Structural Equation Model (SEM) to test the hypothesis. Findings: The results show that brand credibility has a positive effect on attitude toward brand and brand loyalty, brand experience has a positive effect on brand loyalty. Attitude toward the brand mediates the effect of brand credibility and brand brand loyalty, either partially or fully through mediation. Implications: Thisxstudyxprovides a practicalxframeworkxforxthe marketing department of each android smartphone manufacturer that can explain how a brand credibility and brand experience created by the company can form brand loyalty, which is influenced directly or through mediation from attitude toward brand. consumers to each of these companies. So, the companies that oversee smartphone brands such as Samsung, Xiaomi and Oppo can maintain current policies to achieve a better level of brand loyalty in the future. In the long term, research on these variables will also help the marketing department to periodically check the proposed level of influence and compare it with previous results. If the value of the proposed influence can increase or remain at the same level, then the company can maintain the current policy on these variables. Originality: This research can contribute by proposing brand credibility, attitude toward brand and brand loyalty in a single model or separately. In addition, this study adds to other literature that also influences brand loyalty, namely brand experience because the experience of today's consumers is also an important thing that cannot be ignored